The immunomodulatory effect of Glagah consortium microalgae polysaccharides based on splenocyte proliferation and cytokine production in vitro - ZHAZA AFILILLA; Lucia Tri Suwanti Suwanti; MUFASIRIN MUFASIRIN; HENI PNY KOERNIAWAN; MOCHAMAD DONNY KOERNIAWAN; EKO AGUS SUYONO; ARIEF BUDIMAN; ULFAH JUNIARTI SIREGAR (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Afililla Z, Suwanti LT, Mufasirin, Koerniawan HP, Suyono EA, Budiman A, Siregar UJ. 2022. The immunomodulatory effect of Glagah consortium microalgae polysaccharides based on splenocyte proliferation and cytokine production in vitro. Biodiversitas 23: 5205-5209. Indonesia is known as a maritime country that has various organisms, including microalgae. Some microalgae have many bioactivities, such as immunomodulatory activity. This study aimed to determine Glagah consortium microalgae polysaccharide (GCMP) and polysaccharide of Spirulina platensis (PSP) as an immunomodulator based on its effect on splenocyte proliferation and cytokine production in vitro. Crude polysaccharides were extracted by lye extraction method. Splenocytes were obtained from spleen of healthy mice and cultured in RPMI 1640 medium with and without Concanavalin A (Con A). Cells (3×105 per well) were treated with polysaccharide with dose gradually 0, 1.25, 2.5, 10 and 20 µg/mL. Splenocytes proliferation were observed by 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay. The supernatant was taken for the detection of cytokines using enzyme-linked immunoassay (ELISA). The results showed that GCMP, both with and without Con A at a concentration of less than 10 mg/mL decreased cell viability, on the other hand, a concentration of 10-20 mg/mL had a proliferative effect. Splenocytes were shown a proliferative effect at all concentrations of PSP, both with and without Con A. The concentration of polysaccharides, both GCMP and PSP, did not affect cytokine levels. In conclusion, based on the proliferation of splenocytes, GCMP has an immunomodulatory effect depending on its concentration.